2021
DOI: 10.2991/aer.k.210121.031
|View full text |Cite
|
Sign up to set email alerts
|

The Creative Hub: HR Strategic Function in The Digital Age

Abstract: The function of managing human resources in organizations has evolved. The adaptability of the human resource management function in the organization is important, so that it is agile in responding to the demands of the times and able to contribute strategically to the performance and competitive advantage of the organization in a sustainable manner. In the digital age, technology-based HR transformation is needed to meet the needs of that era. To carry out technology-based HR transformation, the transformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Business acumen creates an understanding of the business, including internal and external drivers, influencing the organisation's direction (Fahim, 2018). Junita (2021) has proposed that business acumen, as a skill, allows HRBPs to engage with managers, with the organisational mandate being the most important. Sun (2019) argues that credibility in the HRBP and senior manager engagement is built by the HRBP's ability to illustrate an in-depth understanding of how the business units operate, particularly in a JMER, 2022, 03(2), 106─120…”
Section: Discussionmentioning
confidence: 99%
“…Business acumen creates an understanding of the business, including internal and external drivers, influencing the organisation's direction (Fahim, 2018). Junita (2021) has proposed that business acumen, as a skill, allows HRBPs to engage with managers, with the organisational mandate being the most important. Sun (2019) argues that credibility in the HRBP and senior manager engagement is built by the HRBP's ability to illustrate an in-depth understanding of how the business units operate, particularly in a JMER, 2022, 03(2), 106─120…”
Section: Discussionmentioning
confidence: 99%
“…While exploring the psychological frames of HR professionals, Labedz and Lee (2011) found that these professionals do not have a strategic outlook yet have shown people-oriented behaviors. Ulrich et al (2008) (Junita, 2021). Moreover, HR professionals have to take responsibility for the process of developing strategy regularly.…”
Section: Strategy Architect and Hr Professionals' Effectivenessmentioning
confidence: 99%
“…Culture and change have been acknowledged as an influential factor in examining the performance of an organization ( Wilkins and Ouchi, 1983 ; Jones et al, 2005 ). According to Dhanpat et al (2020) and Junita (2021) , the change agent is one who embraces change in the organization, responds actively to the change, and lets people know how to deal with the change. Ulrich et al (2008) argue that culture has been an essential feature in HR competency studies since 1997.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the authoritative assets that play a significant part in accomplishing objectives is Human Resources, the quickly changing business climate requests the job of HR's upper hand (Junita, 2021). HR is the way to confront the time of the advanced economy.…”
Section: Introductionmentioning
confidence: 99%